دراسة غزارة المنخربات البلانكتونية في توضعات الميوسين الأدنى في حوض نهر الكبير الشمالي وأهميتها الجيولوجية (Latakia University Journal -Basic Sciences Series, 2016)
The lithological study and micropaleontological analyses of 21 samples taken from four geological sections of lower Miocene deposits led to a stratigraphic study for determination of enrichment of planktonic species in these deposits . These species were combined with biozones of lower miocene and their stratigraphic distribution in the studied sections according to planktonic foraminifera of worldwide spreading . This study contributed in understanding of paleogeographic development of Neogene basin within this period of time , which appeared as a marine progress in lower Miocene , which continued up to upper Miocene in the northwestern part of Syria . The sediments of lower Miocene consisted of marl , clay marl deposits with interfacial layers of clay and limestones or marl limestones deposited unconformithy with nummoliticlimestones of Eocene , or cretaceous carbonates rich in betome sometimes .قادت الدراسة الليتولوجية والتحاليل المكروباليونتولوجية للعينات المأخوذة وعددها(21 ) عينة من أربعة مقاطع جيولوجية في توضعات الميوسين الأدنى إلى إجراء دراسة إحصائية وتحديد غزارة الأنواع البلانكتونية(العوالق)المرافقة للنطاقات الإحيائية في الميوسين الأدنى وتوزعها الاستراتغرافي في المقاطع المدروسة استناداً إلى منخربات بلانكتونية مميزة ذات انتشار عالمي , كما ساهمت هذه الدراسة في فهم التطور البالبوجغرافي للحوض النيوجيني في هذه الفترة من الزمن , الذي تجلى بتجاوز بحري ميوسيني على الشمال الغربي من سوريا استمر حتى الميوسين الأعلى .تتألف رسوبات الميوسين الأدنى من توضعات مارنية , مارنية غضارية مع تداخلات من أحجار كلسية غضارية أو مارنية كلسية مستقرة بعدم توافق فوق صخور الايوسين الكلسية النيموليتية أو الكربوناتية الكريتاسية المشربة بالبيتوم أحياناً .